Treatise and Commeontary on the Prevention of Money Laundering Act 2002 Vol 1 Sections 1-24 - K K Khandelwal; Singh, Anu (Haryana Oak Bridge Publishing Pvt Ltd, 2025)
Dive deep into the intricacies of financial crime prevention with this comprehensive two-volume set on The Prevention of Money Laundering Act, 2002. Written by Dr K K Khandelwal, this 2025 edition serves as both a detailed treatise and practical commentary, offering invaluable insights for legal professionals, compliance officers, and financial institutions. The work meticulously examines the legislative framework, judicial interpretations, and regulatory developments surrounding money laundering prevention in India. Each volume systematically breaks down complex legal concepts, providing readers with clear explanations and expert analysis. Whether you're a practicing lawyer, academic, or compliance professional, this authoritative resource will help you navigate the complexities of anti-money laundering legislation and its practical applications.
Keywords: Law; Banking; Evolution Concepts Analysis And Case Law